Introduction: Understanding social media monopolies - Patelis, Korinna; Hatzopoulos, Pavlos (My University, 2013)
The ubiquitous presence of social media in everyday life has not been met by equally pervasive research efforts for their critical understanding, due mostly to the increasing specialization and fragmentation of academic research. Unlike Us: Understanding Social Media Monopolies attempts to set out a research platform that overcomes both the dominant quantitative analyses and the privacy paradigm in current social media research.
Keywords: Social media; Monopolies